ANALYSIS OF INDONESIAN NATURAL RUBBER EXPORT DEVELOPMENT PERFORMANCE IN THE UNITED STATES MARKET - Zakki Muhtaram; Safrida; Sofyan (CV. Radja Publika, 2024)
This research aims to determine the factors influencing Indonesian natural rubber exports to the United States. This research was conducted in March-May 2024. This quantitative research uses the 2 SLS (Two Stage Least Square) method with a simultaneous equation model. The data used is secondary data obtained from Trademap, the World Bank, and the Directorate General of Indonesian Plantations over 20 years (2001-2022). The results of the research show that in the equation for Indonesian natural rubber exports to the United States, the variables that have a significant influence are the variables namely Indonesian rubber prices, United States rubber prices, Indonesian rubber production, rubber production from competing countries, United States gross domestic product, export quota limitation policies, and United States inflation simultaneously has a significant influence on the variable of Indonesian rubber exports to the United States. In the Indonesian rubber price equation, the variables of world rubber prices, Indonesian rubber production, rubber prices of competing countries, demand for Indonesian rubber, total Indonesian exports, and export quota limitation policies simultaneously significantly affect the Indonesian rubber price variable. In the United States rubber price equation, world rubber prices, United States rubber substitute prices, and Indonesian rubber demand simultaneously significantly affect the United States rubber price variable.